Analysis of Factors Affecting The Quality of Life in Vitiligo Patients at Dermato-Venereology Polyclinic dr. Zainoel Abidin General Hospital, Banda Aceh - Fitria Fitria; Vera D. Mulia; Hafni A. (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Vitiligo is a skin depigmentation disorder and chronic asymptomatic due to the destruction of melanocytes. Patients with vitiligo in addition to physical disorders also affect the psychological state that disrupts the quality of life of the patients. This study aims to identify the factors that affect the quality of life of vitiligo patients. Analytic study was conducted using cross-sectional design with questionnaire Dermatology Life Quality Index (DLQI) to vitiligo patients who went to the Dermato-Venereology Policlinic dr. Zainoel Abidin General Hospital, Banda Aceh. The results of this study found that visible location and long-suffering vitiligoless than one year affect the quality of life of patients (p0.05) which the duration of suffering vitiligomore influence than vitíligo location.